2009
DOI: 10.1590/s1806-37132009001000008
|View full text |Cite
|
Sign up to set email alerts
|

Efeito do incentivo alimentício sobre o desfecho do tratamento de pacientes com tuberculose em uma unidade primária de saúde no município de Duque de Caxias, Rio de Janeiro

Abstract: Objective: To evaluate the effect that the distribution of food baskets to tuberculosis (TB) patients has on treatment outcomes at a primary health care clinic. Methods: Retrospective comparative study of the medical and social aspects of 142 patients at a primary health care clinic in the city of Duque de Caxias, Brazil. The patients were divided into two groups: the first group included 68 patients treated with standard regimens (between September of 2001 and December of 2003); and the second group included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 6 publications
0
20
0
4
Order By: Relevance
“…Assim, a consulta em menos de 24 horas se efeito adverso, faz com que a taxa de abandono diminua, aumentando a adesão. Sobre a oferta de cesta básica ou vale alimentação, autores afirmam que, com o oferecimento de cestas básicas, houve um aumento significativo da adesão ao tratamento 16,17 . Os autores pressupõem que o fornecimento de alimentação, de alguma forma interfere nos fatores de abandono como a baixa escolaridade, desemprego, renda e fome, influenciando diretamente na adesão ao tratamento.…”
Section: Resultsunclassified
“…Assim, a consulta em menos de 24 horas se efeito adverso, faz com que a taxa de abandono diminua, aumentando a adesão. Sobre a oferta de cesta básica ou vale alimentação, autores afirmam que, com o oferecimento de cestas básicas, houve um aumento significativo da adesão ao tratamento 16,17 . Os autores pressupõem que o fornecimento de alimentação, de alguma forma interfere nos fatores de abandono como a baixa escolaridade, desemprego, renda e fome, influenciando diretamente na adesão ao tratamento.…”
Section: Resultsunclassified
“…The findings showed that food basket allocation could be a beneficial approach to improve adherence to TB treatments in primary care. 50 nUtrıtıonal sUpport and cUre rate A retrospective comparative study was carried out among 142 patients at the Duque de Caxias primary hospital in Brazil. There were 2 groups of samples:…”
Section: Nutrıtıonal Status and Adherence/complıance Of Treatmentmentioning
confidence: 99%
“…The analysis between the two groups found that the cure rate was higher compared to standard regime group (87.1% vs. 69.7%) in food basket group. 50…”
Section: Nutrıtıonal Status and Adherence/complıance Of Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…There is also evidence showing a 7% higher cure rate among “Bolsa Família” beneficiares in Brazil [39], and a positive impact of social protection interventions (CRESIPT project) on catastrophic cost in poor households in Peru [40]. Siroka et al [40] also suggested a strong negative correlation between expenditures as gross domestic product (GDP) percentage in social protection programs for poverty alleviation and TB rates (for incidence, prevalence and mortality) [41]. …”
Section: Tuberculosis Control Among Migrantsmentioning
confidence: 99%